Carbon-based catalysts derived from biomass for the production of biodiesel from low quality fats - Ganaserkhar, Shobhana (2020)
Increase in awareness of the depletion of fossil duel resources makes biodiesel, a promising substitute of an alternative fuel. It is proved that biodiesel to be the best replacement for diesel because of its unique properties like significant reduction in greenhouse gas emissions, non-sulfur emissions, non-particulate matter pollutants, low toxicity and biodegradability. However, the cost of biodiesel is the major obstacle to its commercialization in comparison to petroleum-based diesel fuel. The high cost is primarily due to the raw material, mostly vegetable oil that are used as feedstock and utilization of catalyst. Thus in this study, biodiesel are studied using high free fatty acid feedstock (Chicken Fat and Skin Oil (CFSO) and Palm Fatty Acid Distillate (PFAD)). Simultaneous esterification and transesterification of chicken fat oil (CFSO) over Ce supported ACcs catalyst that are treated using sulphuric acid and details study on the effect of Ce concentration from range 5 to 15 wt. % also further investigated. The results showed that 5wt. % Ce was an optimum concentration for optimizing the esterification and transesterification of CFSO with free fatty acid (FFA) conversion approximately 93%. For PFAD feedstock esterification reaction were conducted over chlorosulfonated treated carbon catalyst from various sources (Commercialized carbon (CC), Multi-Wall Carbon Nanotube (MWCNT) and carbon derived from coconut shell (CS)). Finding reveals FFA conversion increased followed the order of CCs>MWCNT>CSs. The biodiesel production both studies were optimized via one-variable –at-a –time (OVAT) by varying methanol to CFSO or PFAD, catalyst loading, reaction time and temperature. Optimization study using CFSO feedstock revealed at usage of 0.3wt% catalyst loading, 1:12 CFSO molar ratio to methanol within 1 hour reaction time at 90°C generated 93%. Whereas, chlorosulfonated carbon exhibited good catalytic activity with high FFA conversion of 95% at optimum parameter of 1:14 PFAD molar ratio to methanol, 0.5wt% of catalyst loading an 80°C reaction temperature within 2 hours reaction time.